Pengembangan Modul Pembelajaran IPABerbasis STEM Pjbl Untuk Meningkatkan Kemampuan Pemecahan Masalah Peserta Didik Pada Materi Usaha, Energi Dan Pesawat Sederhana - Laily Diva Az Zahra; Yasmine Khairunnisa; Mella Mutika Sari (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2026)
This study aims to develop a STEM-based science learning module using the Project-Based Learning (PjBL) approach to improve students' problem-solving skills. The research design follows the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. A total of 31 students from a single class participated in the learning process using the developed module. The data collected included pretest and posttest scores, as well as student response questionnaires regarding the module. The analysis results indicate that the STEM-based PjBL science learning module is highly valid, with a score of 0.80 based on Aiken's V calculation. Additionally, there was a significant improvement in students' problem-solving abilities, as shown by the increase in average pretest scores from 57.65 to 79.61 after using the module. This suggests that the developed module is effective in enhancing students' problem-solving skills. Furthermore, student feedback on the module was positive, with a total score of 85%, indicating that it is very practical and beneficial for the learning process. This research makes a significant contribution to the development of innovative and effective teaching methods.